Factors Affecting Adoption of Mobile Services - Allil, Kamaal; Khan, Mohammed Naved (International Review of Management and Marketing, 2016)
The extent of adoption of mobile services in India has not progressed as expected. In this backdrop, the present research investigated factors affecting intention to adopt mobile services. Using researcher controlled sampling, data was generated from students enrolled in business schools. Two sets of statistical techniques were employed. The first set was used to refine and test the validity and reliability of the research instrument by using Cronbach Alpha, inter-item and item-total correlation, and principal component analysis. The second set was used to estimate interrelated dependence relationships by using Structural Equation Modelling. Mobile Service Adoption Model was proposed. Results suggest that attitude, compatibility, subjective norm, perceived usefulness, and personal innovativeness are significant determinants of intention to adopt mobile services. The findings can be of vital importance to practitioners when developing new services and strategizing marketing campaigns. The study also opens up several avenues for additional research in the domain of adoption of mobile services. Keywords: Mobile services adoption; India. JEL Classifications: M300; M310